Identification of two distinct phosphoproteins as components of the human B cell antigen receptor complex - Van Noesel, C J; Borst, J; De Vries, E F; Van Lier, R A (European journal of immunology, 1990)
In human B cells, the molecules that, upon receptor occupancy, couple membrane immunoglobulin to intracellular signal transduction pathways have never been identified. We here describe two phosphoproteins as integral parts of the B cell antigen receptor complex. Membrane IgM is non-covalently associated with a disulfide-linked heterodimer of glycoproteins. These molecules can be demonstrated on B cell lines and freshly isolated polyclonal B cell populations and are subject to phosphorylation at serine residues. Identification of these constituents of the B cell receptor complex opens up the opportunity to study coupling of the B cell antigen receptor to the intracellular signal transduction machinery at the molecular level.